Fostering university-industry linkage - Universiti Putra Malaysia, Bahagian Komunikasi Korporat (Universiti Putra Malaysia, 2014)
Strengthening the linkage between academic research and the business world is vital if we want to move the great ideas to the marketplace, according to national ICT research and development agency, MIMOS. As a strategic agency under MOSTI, MIMOS recognises universities as sources and repositories of knowledge, innovation and technological advances.